UJI AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOL DAUN SUJI(Dracaena angustifolia) DENGAN METODE DPPH (1,1-difenil-2-pikrilhidrazil) - Putriyana Putriyana; Ridwanto (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2022)
The results of this study indicate that; 1) The screening results for simplicia and the ethanol extract of suji leaves (Dracaena angustifolia) showed positive results for flavonoids, saponins, tannins and steroids/triterpenoids. 2) The antioxidant activity of suji leaves (Dracaena angustifolia) shows strength in the "strong" category with an IC50 value of 48.96 ppm